Chapter Resistenza all'acquisizione della struttura del discorso e della gerarchizzazione sintattica in un corpus acquisizionale italo-russo - STOYANOVA, Nataliya (Biblioteca di Studi Slavistici, 2016)
In this paper we present some statistics data regarding the preferential choices of native speakers of Russian and Italian and of Italian speakers of Russian with respect to the discourse structure and syntactic hierarchy. The research was conducted on the material of an original acquisition corpus, and has demonstrated that the discourse level is more resistant to the acquisition of the second language norms than the macrosyntactic level.